Maturation of the auditory t‐complex brain response across adolescence. Issue Volume 31:Issue1(2013:Feb.) (15th October 2012) - Mahajan, Yatin; McArthur, Genevieve
Abstract: Adolescence is a time of great change in the brain in terms of structure and function. It is possible to track the development of neural function across adolescence using auditory event‐related potentials (ERPs). This study tested if the brain's functional processing of sound changed across adolescence. We measured passive auditory t‐complex peaks to pure tones and consonant‐vowel (CV) syllables in 90 children and adolescents aged 10–18 years, as well as 10 adults. Across adolescence, Na amplitude increased to tones and speech at the right, but not left, temporal site. Ta amplitude decreased at the right temporal site for tones, and at both sites for speech. The Tb remained constant at both sites. The Na and Ta appeared to mature later in the right than left hemisphere. The t‐complex peaks Na and Tb exhibited left lateralization and Ta showed right lateralization. Thus, the functional processing of sound continued to develop across adolescence and into adulthood.